Diagnosing adrenal insufficiency using ACTH stimulation test. Issue 2 (6th August 2020) - Lipworth, Brian; Chan, Rory; Kuo, Chris RuiWen
We read with interest the real-world data of Nanzer et al. [1], looking at adrenal insufficiency (AI) in severe asthma patients taking oral corticosteroid-sparing anti-interleukin (IL)-5 therapy. They reported that 43% of patients apparently failed a short adrenocorticotropic hormone (ACTH) stimulation test associated with a median baseline morning serum cortisol of 86 nmol·L −1 and a median prednisolone dose of 5 mg. We would be interested to know the mean cortisol level after ACTH, as well as the percentage of patients who failed to achieve a post-ACTH level of 500 nmol·L −1 which is the accepted cut-off for impaired response [2, 3]. Low dose ACTH stimulation test is more likely to detect adrenal insuffiency in patients being weaned off oral corticosteroids https://bit.ly/2XsMA3i